Metabolic-associated Fatty Liver Disease Regulation through Nutri Epigenetic Methylation - Rivera-Aguirre, Jesus; López-Sánchez, Guillermo Nahúm; Chávez-Tapia, Norberto C.; Uribe, Misael; Nuño-Lámbarri, Natalia (Mini Reviews in Medicinal Chemistry, 2023)
Metabolically associated fatty liver disease, formerly called nonalcoholic fatty liver disease, is the most common liver disease globally, representing the third cause of liver transplantation. Metabolically associated fatty liver disease is defined as having more than 5% lipid droplets in hepatocytes without other concomitant liver diseases. Various stimuli such as the secretion of inflammatory cytokines, mitochondrial and endoplasmic reticulum dysfunction due to oxidative stress, alteration of the intestine-liver axis, bacterial dysbiosis, as well as genetic and epigenetic factors can modify the progression of metabolically associated fatty liver disease to fibrosis, cirrhosis, and may reach hepatocellular carcinoma. Epigenetics is responsible for a highly sophisticated regulatory system that controls many cellular processes in response to multiple environmental factors as an adaptive mechanism unrelated to alterations in the primary deoxyribonucleic acid sequence, including gene expression, microRNAs, DNA methylation, modifications in histones, and DNA-protein interactions. Several studies have shown that epigenetic changes are associated with various diseases, including metabolically associated fatty liver disease. Nutri epigenomics is the interaction between nutrition and components at the transcriptional or post-transcriptional level. Methylation processes involve micronutrients that regulate epigenetic states in a physiological and pathological context. Micronutrients such as methionine, folate, and choline are the main components of one-carbon metabolism, functioning as methyl group donors, and their deficiency predisposes to various pathologies such as metabolically associated fatty liver disease. Understanding of epigenetic modifiers leads us to develop new therapeutic therapies for patients with metabolically associated fatty liver disease.
Keywords: liver